Is the impact of COVID-19 on housing construction activity inside and outside a large city evident? The example of Łódź (Poland) - Załęczna, Magdalena; Antczak-Stępniak, Agata (Bulletin of Geography. Socio-economic Series, 2022)
The coronavirus pandemic has influenced cities’ shape and future. Telecommuting, teleconferencing, telelearning and e-commerce are creating a new environment of human life. These new factors should be added to the existing problems of urbanisation that are urban sprawl and depopulation. The authors of the paper decided to examine the intensity and spatial distribution of residential construction activity and residential real-estate trade in one of the biggest Polish cities – Łódź – and neighbouring municipalities to answer the question of whether the pandemic has affected housing decisions taken by developers and buyers. Based on statistical data, attempts were made to observe new signs confirming the intensification or weakening of past trends. The research was based on desk research and comparative analysis.